Improved PNC selection criteria and process for IEEE802.15.3. - Sulaiman, Thafer H. (IEEE Communications magazine)
IEEE 802.15.3 is a standard that supports high data rate for wireless personal area networks. It implements a centralized topology for network monitoring and control. The centralized piconet coordinator (PNC) needs to be dynamically selected depending on a number of categories that measure its abilities as the most capable device compared to the surrounding devices in the network. This article presents an extension to the PNC selection criteria in IEEE 802.15.3 by modifying the reserved fields readily available in the standard to support user-centricity as well as other higher layer service dependent criteria. This article also develops the implementation process for the message header exchange between devices to support this new selection process. In addition, simulations are carried out that show the proof of concept of the manner in which this new criteria could be implemented in IEEE 802.15.3.